Pengaruh Rias Wajah Karakter Dua Dimensi terhadap Penjiwaan Tokoh pada Pertunjukan Drama Teater di FBS UNP - Khaira, Nadiratul; Silvia, Febri (TSAQOFAH, 2025)
This study aims to examine the influence of two-dimensional character makeup on actors’ ability to internalize their roles in drama and theater performances at the Faculty of Languages and Arts, Universitas Negeri Padang (FBS UNP). In the theatrical context, character makeup plays a vital role in reinforcing character identity and assisting actors in immersing themselves in their roles. The two-dimensional makeup technique emphasizes the use of lines, colors, and shapes applied directly to the face without prosthetic materials, enabling the creation of bold and expressive visual characters. This research employs a quantitative descriptive approach, involving 68 students from the Performing Arts Study Program who actively participate in theater productions. Data analysis included tests for normality, linearity, heteroscedasticity, simple linear regression, and hypothesis testing. The results show that two-dimensional character makeup has a significant effect on role internalization, as indicated by a significance value of 0.000 (< 0.05) and a correlation coefficient of 0.458. These findings suggest that the more effectively the two-dimensional makeup technique is applied, the deeper the actor’s emotional engagement and embodiment of the character becomes. Thus, character makeup functions not only as a visual element but also as an emotional support tool in the acting process.